Relations between peer bullying and adolescent depression: the mediating effect of cellphone usage - Shen, Ying; Zhou, Yongjie; Ren, Shuyang; Li, Yanyan; Liu, Yongshi; Zhou, Rong; Fan, Xiwang; Xie, Guangping (Frontiers in Psychiatry, 2025)
IntroductionAdolescent depression is a growing concern worldwide. This study explores the relationship between peer bullying, cellphone usage, and adolescent depression, aiming to investigate a mediation effect model based on Erikson’s stages of psychological development.MethodsUsing a cluster sampling method and a cross-sectional survey, a total of 2343 adolescents aged 12 to 18 were recruited from 12 national medical institutions. Cluster sampling was used to select participants who were confirmed to have depression. The survey employed the Multidimensional Peer Victimization Scale (MPVS), the Mobile Phone Addiction Index (MPAI), and the Patient Health Questionnaire (PHQ-9) for paper-and pencil evaluations. The three variables were analyzed using SPSS 26 software, applying correlation analysis and multiple linear regression analysis.ResultsThe results showed that peer bullying has significant positive correlation with depression (r=0.330, p<0.001) and with cellphone use (r=0.287, p<0.001). Furthermore, cellphone usage was positively correlated with depression (r=0.333, p<0.001). Additionally, cellphone usage had a partial mediating effect between peer bullying and depression (r=0.414, p<0.001, b=0.234). The results underscore the crucial role of peer relationships in adolescent psychological development. Cellphone addiction mediates the link between adolescent depression and peer bullying, highlighting its significant impact.ConclusionThese findings contribute to understanding the interplay between social influence and depression, offering practical guidelines for fostering a supportive school environment and regulating adolescents’ phone use.